A teoria híbrida das emoções em Platão: uma abordagem entre cognitivismo e não cognitivismo - Guterres, Guilherme Santos (Universidade do Vale do Rio dos Sinos, 2024)
This thesis explores the problem of emotional identity in Plato's philosophy, situating his hybrid approach within the contemporary debate between cognitive and non-cognitive theories. Through a comparative bibliographic methodology, we propose that Plato's hybrid approach presents emotions as states that encompass and integrate elements from both theories within a holistic, non-reductive perspective. The work is divided into three main chapters. The first chapter critically examines three theoretical approaches to the problem of emotional identity: Martha Nussbaum's cognitive-evaluative theory, Jesse Prinz's embodied appraisal theory, and the hybrid theories of Peter Goldie, Bennett Helm, and Jan Slaby. We pay particular attention to the first two theories, regarded as the state of the question in the debate on the investigated relationship. As a secondary objective, we position ourselves relative to these theories, arguing in favor of a hybrid or integrative approach between both perspectives. In the second chapter, we begin to clarify Plato’s approach to the identity of emotions by reconstructing his Theory of the Tripartite Soul, based on the Republic and Phaedrus dialogues. We highlight the interdependent relationship between the parts of the soul in Plato, emphasizing the holistic perspective he adopts in treating emotions as mediators between the poles of logistikon (“rational part”) and epithumetikon (“desiring part”). The third chapter analyzes Plato’s Philebus dialogue, where we find a nuanced version of his hybrid approach. In the Philebus, emotions are described as mixtures (meixis) of pleasure and pain, involving memory (mneme), sensory perception (aisthesis), desire (epithymia), and imagination (phantasia). In this framework, Plato proposes a hybrid approach to emotions, viewing them as complex phenomena resulting from the dynamic interaction of different faculties of the soul. Finally, we show that by transcending the dichotomies between cognitive and non-cognitive theories, Plato also offers a compatibilist perspective on emotions that enriches the contemporary debate on their identity, emphasizing the need for a more comprehensive and integrated understanding of emotional states.
Keywords: Platão; Teoria das emoções; Abordagem híbrida; Cognitivismo; Não cognitivismo; Plato; Theory of emotions; Hybrid approach; Cognitivism; Non-cognitivism; ACCNPQ::Ciências Humanas::Filosofia